Relationship between the Real Estate Sector and the Stock Market in Chinese Provinces - Zeyu Di; Almas Heshmati; Sijia Liu (Institute of Labor Economics (IZA), 2022)
In China, real estate and the stock market are the two main markets favored by both individual and institutional investors. There is a significant economic link between the two. Therefore, their relationship and long-term and short-term causality can provide good guidance for investors. This paper studies the causality and correlation relationship between the stock market and real estate sector's trading volumes in 31 provinces of China. Its empirical results are based on panel data from 2000 to 2016. Various panel unit root, co-integration, and model specification and estimation tests are carried out. The panel mean group is found to be the most suitable method for the analysis. The study finds that the main industries in different provinces may affect the short-term causal relationship between the real estate sector and the stock market. But in the long-run, the causal relationship between the two is 2-way and stable.
Keywords: E22; H54; O16; O18; R53; 330; real estate; stock market; causal relationship; asset allocation; portfolio; economic area; Chinese provinces